Pengaruh kegiatan Online Research Skills (ORS) Perpustakaan Pusat UIN Maulana Malik Ibrahim Malang terhadap peningkatan kualitas riset mahasiswa Program Studi Psikologi - Adi Sucipto (IJAL (Indonesian Journal of Academic Librarianship), 2023)
The ORS activity has been carried out since 2013, becoming a weekly agenda of the Center Library of UIN Malang. It is for students who are interested and want to develop their writing and research skills. The ORS learning materials include scientific information sources, scientific information search strategy, scientific information source management, reference management software use, and research ethics. The psychology Study Program supports its students to improve their research by conducting collaborative research programs and competitive student research. The output consists of research in the field of psychology. The research subject consists of psychology students at the end of their studies since they have finished some courses dealing with research and are taking their research for their thesis. The researcher employed a quantitative method and simple linear regression analysis. The data analysis result shows that the ORS of the Center Library of UIN Malang significantly influences psychology students’ research quality improvement. The simple linear regression analysis results show that the determination coefficient is 0.472. Therefore, the ORS activity affects psychology students’ research quality improvement for 47%, and the rest, 47%, is other factors not included in the research. The ORS activity of the Center Library of UIN Malang significantly influences psychology students’ research quality improvement. It can be seen from the result of the simple linear regression showing a correlation of R 0.687. Hence, the researcher concludes that the ORS activity has a significant level of influence on psychology students’ research quality improvement.